Hemocyte Clusters Defined by scRNA-Seq in Bombyx mori: In Silico Analysis of Predicted Marker Genes and Implications for Potential Functional Roles - Feng, Min; Swevers, Luc; Sun, Jingchen (Frontiers in Immunology, 2022)
Within the hemolymph, insect hemocytes constitute a heterogeneous population of macrophage-like cells that play important roles in innate immunity, homeostasis and development. Classification of hemocytes in different subtypes by size, morphology and biochemical or immunological markers has been difficult and only in Drosophila extensive genetic analysis allowed the construction of a coherent picture of hemocyte differentiation from pro-hemocytes to granulocytes, crystal cells and plasmatocytes. However, the advent of high-throughput single cell technologies, such as single cell RNA sequencing (scRNA-seq), is bound to have a high impact on the study of hemocytes subtypes and their phenotypes in other insects for which a sophisticated genetic toolbox is not available. Instead of averaging gene expression across all cells as occurs in bulk-RNA-seq, scRNA-seq allows high-throughput and specific visualization of the differentiation status of individual cells. With scRNA-seq, interesting cell types can be identified in heterogeneous populations and direct analysis of rare cell types is possible. Next to its ability to profile the transcriptomes of individual cells in tissue samples, scRNA-seq can be used to propose marker genes that are characteristic of different hemocyte subtypes and predict their functions. In this perspective, the identities of the different marker genes that were identified by scRNA-seq analysis to define 13 distinct cell clusters of hemocytes in larvae of the silkworm, Bombyx mori, are discussed in detail. The analysis confirms the broad division of hemocytes in granulocytes, plasmatocytes, oenocytoids and perhaps spherulocytes but also reveals considerable complexity at the molecular level and highly specialized functions. In addition, predicted hemocyte marker genes in Bombyx generally show only limited convergence with the genes that are considered characteristic for hemocyte subtypes in Drosophila.